Contemporary approaches to informatization of educational process in higher education in Ukraine - Pavliuk, Roman (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article describes the modern approaches to the informatization of educational process in higher educational institutions of Ukraine. The relevance of introducing of and its regulatory framework are investigated and the views of scientists to the definitions of "distance learning" and "information-educational environment" are summarizes. The system of work with students using distance learning courses "Business Foreign Language" and "Modern children's literature English-speaking countries" is shown on the example of BorysGrinchenko Kyiv University (Kyiv, Ukraine). The results of investigation based on a survey of students at the beginning and end of the distance courses work demonstrated that the use of distance learning coursespromotes to the self-organization of the student, improving computer skills, facilitates the process of self-learning.